Meta AI for High School Students: A Suitable Tool to Improve English Writing Skills - Irda Fitriana HS; Yeni Rahmawati; Sunarti (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
In the current digital era, the integration of artificial intelligence (AI) into education has significantly reshaped how students access and engage with learning materials. Among various innovations, AI-powered tools such as Meta AI have gained attention for their potential to assist students in developing essential language skills, particularly in English writing. As writing remains a fundamental yet challenging aspect of language learning, it is important to understand how students perceive the role of AI tools in supporting their academic progress. This study investigates high school students’ perceptions of Meta AI as an accessible and affordable platform for improving their English writing skills. Grounded in the context of the growing presence of AI in education, the study examines three core dimensions: accessibility, affordability, and perceived effectiveness in writing development. A quantitative descriptive method was used, employing a structured questionnaire administered to 78 vocational high school students in Samarinda, Indonesia. The findings indicate that most students find Meta AI easy to access and use, particularly across commonly used devices and in both school and home settings. Students also perceive the platform as cost-effective, reporting no need for financial investment or expensive equipment. In terms of writing support, students agree that Meta AI helps improve grammar, expand vocabulary, and organize ideas more clearly. However, some challenges were identified, such as limited functionality under slow internet conditions and mixed perceptions when comparing Meta AI to paid writing tools. This study suggests that Meta AI holds promise as a democratizing tool in English writing instruction, especially in resource-limited educational environments. The results underscore the importance of improving digital infrastructure and developing strategies to enhance user engagement for long-term learning benefits.